Investment, leverage and political risk: Evidence from project-level FDI - King, Timothy; Loncan, Tiago; Khan, Zaheer (Journal of Corporate Finance, 2021)
Does capital structure influence firms' FDI capital expenditure decisions into countries with varying degrees of political risk? We explore this question using a novel dataset that matches 10,000 unique outward foreign direct investment (OFDI) projects with 1135 distinct U.S. firms over the period 2003–2014. We find that capital expenditures allocated to FDI projects are significantly lower for highly leveraged firms, in particular for firms with low growth opportunities. Firms also commit lower capital amounts to investments located in countries characterized by higher political risk. Furthermore, leverage and political risk interact with one another in determining the financial commitment of the FDI, with leverage exerting a significantly stronger negative effect on capital expenditures in countries where political risk is elevated. Our findings are consistent with the monitoring role of debt in curbing exposure to political risk in multinational firms' foreign operations, and corroborate the disciplinary role of leverage on firms' investment decisions.